Analisis Saluran Pemasaran Melon Kuning di Kecamatan Pantai Labu Kabupaten Deli Serdang - Gaby Oktavia Sembiring; Ahmad Rafiqi Tantawi; Rahma Sari Siregar (Universitas Medan Area, 2021)
This research was conducted with the aim to know the yellow melon’s marketing channel and the efficiency of the yellow melon marketing channel in Pantai Labu District. This research is a descriptive qualitative and quantitative research. Determination of research units for yellow melon farmers using the census method, while the sample for traders using the snow ball sampling method, and consumer samples using the incidental sampling method. The results showed that there was only one channel formed in the marketing of yellow melon in Pantai Labu District, that us from farmers to collectors, then to wholesalers, retailers, and finally to consumers. In this marketing, the market divides the qualities of melons into three grades of gimbo, bs, and super. The most efficient yellow melon market is super grade yellow melon with the lowest marketing margin value of 10%, farmer's share value of 70%, and the profit to marketing cost ratio value of 17> 0 or Rp 17, - so the yellow melon marketing channel is efficient.